Blockchain-Based Trusted Data Management with Privacy Preservation for Secure IoT Systems - Haojie Zhou; Hongmin Gao; Zhaofeng Ma; Guanhui Lai (Sensors)
With the explosive growth of the Internet of Things (IoT), the traditional single data sharing scheme has difficulty satisfying the data sharing needs of both same-domain and cross-domain IoT devices. In order to realize efficient data sharing of IoT devices in the same domain with data privacy protection and efficient collaboration between IoT devices in different domains, this paper proposes a trusted data sharing scheme in IoT systems based on multi-channel blockchain. The scheme adopts a multi-channel mechanism to isolate the ledger data between IoT devices of different domains; IoT devices of the same domain utilize hybrid encryption to achieve efficient data sharing through smart contracts, and IoT devices of different domains utilize the CKKS algorithm to achieve cross-domain data sharing with privacy protection through proxy nodes (PNs). In addition, this paper adopts decentralized identity (DID) to achieve autonomous identity management to avoid privacy leakage in IoT devices and adopts InterPlanetary File System (IPFS) to store data files to solve the blockchain storage capacity limitation problem. The security analysis proves that this scheme satisfies the IND-CPA security model, and the performance analysis proves that this scheme has good utility in trusted data sharing of IoT devices.